Bioactivity-guided isolation of compounds with antiproliferative activity from Teucrium chamaedrys L. subsp. sinuatum (Celak.) Rech. F. - Geçibesler, Ibrahim Halil; Demirtas, Ibrahim; Koldaş, Serkan; Behçet, Lütfi; Gül, Fatih; Altun, Muhammed (Progress in Nutrition, 2019)
Purpose: To reach active compounds from aerial parts of Teucrium chamaedrys L. subsp. sinuatum (TCS) under the guidance of anticancer assay. Methods: The active compounds of T. chamaedrys were isolated using chromatographic techniques including column and preparative thin layer chromatography. Isolated compounds were characterized using 1D and 2D NMR techniques and high-resolution HPLC–TOF/MS. In the present study, we evaluated in vitro antiproliferative activities of isolated compounds from TCS using xCELLigence Real Time Cell Analysis system (RTCA). Findings: Three phenolic compounds, namely luteolin-7-O-glucoside (cinaroside, compound 1), 5,6,3’-trihydroxy-7,4’ dimethoxyflavone (nuchensin, compound 2), and (E)-p-coumaroyl-O-β-D-glucoside (compound 3) were isolated for the first time from Teucrium chamaedrys subsp. sinuatum (TCS). The phenolic compounds have antiproliferative effect against the HeLa (Human uterine cancer), C6 (Rat brain tumor) and PC3 (human prostate carcinoma) cells. Conclusions: The results demonstrated that T. chamaedrys subsp. sinuatum and its active components may be suggested as a promising natural antiproliferative agent against HeLa, C6 and PC3 cells.